1961
DOI: 10.2134/agronj1961.00021962005300030010x
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors That Affect Nitrate Accumulation in Forages1

Abstract: Synopsis The level of nitrogen fertilization, the species of forage, the part of the plant, the stage of maturity, and the light intensity all affected greatly the concentration of nitrate in forages. The time of nitrogen fertilization, the kind of nitrogen carrier, the placement of nitrogen fertilizer, and the addition of other plant nutrients had only small effect on the concentration of nitrate in forages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

1968
1968
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 5 publications
(13 reference statements)
2
34
0
2
Order By: Relevance
“…All harvests in all years in the current study showed that nitrate concentration in crabgrass forage increased as nitrogen fertilization increased (P < 0.05). Other researchers have also found similar trends in a number of other cool-and warm-season grasses (5,11,13,15). Although splitting annual nitrogen applications for summer annual forages is widely advocated, little data are available to substantiate this practice (10).…”
Section: Month-yearmentioning
confidence: 84%
“…All harvests in all years in the current study showed that nitrate concentration in crabgrass forage increased as nitrogen fertilization increased (P < 0.05). Other researchers have also found similar trends in a number of other cool-and warm-season grasses (5,11,13,15). Although splitting annual nitrogen applications for summer annual forages is widely advocated, little data are available to substantiate this practice (10).…”
Section: Month-yearmentioning
confidence: 84%
“…Since ammonium is rapidly nitrified to nitrate in most soils, fertiliser form might have little effect on nitrate accumulation (e.g., Crawford et al 1961;Peck et al 1971;Barker 1975). According to Maynard et al 1976), the longer the plant is in contact with nitrate the greater will be the level of nitrate accumulated.…”
Section: Discussionmentioning
confidence: 99%
“…The responses of herbage to nitrogen fertilizer depend on many factors (Crawford et al. 1961), among them, the source and rate of application of N and the interval between application and sampling.…”
Section: Discussionmentioning
confidence: 99%